Association between Maternal Vitamin B12 Status during Pregnancy and Neonatal Outcome - A Cross-Sectional Study - Punjari Purna Jyothi; Manasi Garg; Venkatesh Karthik; D. Senkadhirdasan; Soundararajan Palanisamy; A R Rajasulochana (Nigerian Postgraduate Medical Journal)
Background: Maternal Vitamin B12 deficiency during pregnancy is associated with adverse outcomes, including preterm delivery, spontaneous abortion, intrauterine growth restriction and reduced Vitamin B12 levels in neonates. Aims: This study aimed to assess the impact of maternal Vitamin B12 levels on neonatal outcomes, particularly focusing on anthropometric measurements and Vitamin B12 status in newborns. Subjects and Methods: This prospective study was conducted from February 2023 to January 2024, involving antenatal mothers over 28 weeks of gestation admitted for delivery to a tertiary care hospital. After obtaining ethical clearance and informed consent, blood samples were collected to measure maternal Vitamin B12 levels, which were classified as deficient, insufficient or sufficient. Neonatal outcomes, evaluated immediately after birth, included birth weight, length, head circumference and Vitamin B12 status. Statistical analysis was performed using SPSS version 20.0. The Chi-square test was employed for analysing categorical variables, while one-way ANOVA was utilised for continuous variables. Results: Among the 100 mothers studied, 72% had low Vitamin B12 levels, with 41% being deficient and 31% insufficient. Neonates born to mothers with low Vitamin B12 levels showed higher incidences of low birth weight (9%), small for gestational age (23%), short length (<10th percentile) (5%) and small head circumference (<10th percentile) (1%). Although 7% of newborns had low Vitamin B12 levels, no statistically significant association was found between maternal Vitamin B12 status and neonatal anthropometric measurements. Conclusion: Maternal Vitamin B12 deficiency is associated with adverse neonatal outcomes, including lower birth weight rates. These findings emphasise the critical need for routine screening and supplementation of Vitamin B12 in pregnant women.